The Effectivity of Low Dose Steroid for Reducing Intestinal Inflammation Grade in Mice Model of Sepsis Early Stage - Prasetyo, Medita; Ediningsih, Endang; ., Sarsono (Nexus Biomedika, 2015)
Background: Sepsis is a systemic inflammatory response syndrome, which activates apoptosis of the mucous lining of gastrointestinal tract. The use of steroids as inflammatory therapies in sepsis is still debated. This study aimed to determine the effect of steroid in low dose on intestinal inflammation grade in mice model of Sepsis early stage. Method : This study was an experimental laboratory with the post test only controlled group design. The sample was 25 male Balb/C mice, divided into five groups, namely: control (K1), sepsis (K2), sepsis + low dose steroid (K3), sepsis + moderate dose steroid (K4), sepsis + high dose steroid (K5). The models of sepsis were given cecal inoculums material 4 mg/kgBW/day/i.p for 5 days. Two hours after i.p injection of cecal inoculums, the mice were given dexamethasone with doses 0.05; 0.25; 2.50 mg/kgBW/day/i.v, representing low, moderate, and high dose steroid therapy for 5 days. Histological preparation of intestines was made on day 6, while the anti inflammatory effect of steroid therapy was measured based on inflammatory grading according to Chang et al. Data were analyzed using Kruskal Wallis method and Mann Whitney method. The values of p < 0.05 were considered statistically significant. Result : The study showed grading inflammation of mice within groups were: K1: grade 0 (100%); K2: grade 2 (60%) and grade 3 (40%); K3: grade 0 (40%) and grade 1 (60%); K4: grade 2 (20%) and grade 3 (80%); K5: grade 3 (40%) and grade 4 (60%). There was significant difference between groups: K1-K2 (p = 0.005), K2-K3 (p = 0.007), K2-K5 group (p = 0.020), K3-K4 (p = 0.006), K3-K5 (p = 0.007), K4-K5 (p = 0.042). Conclusion: Low dose steroid effectively reduces intestinal inflammation grade in mice model of sepsis early stage. Keywords: Steroid dose, inflammation grade, sepsis.Â